Pengembangan Panduan Model Pembelajaran Sosiodrama untuk Peningkatan Mahārah Al-Kalām Siswa SMA An Nida' Islamic Boarding School Wonosobo - Shidqil Mubarok (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2019)
This research has been motivated by the struggle of teachers to overcome the difficulty in applying innovative and practical learning models, as they need to understand complexity of teaching textbooks without being provided with a complete explanation. The sociodrama learning model handbook is expected to be useful in overcoming academic problems of Arabic language learning models with sociodrama method. It also to measure the necessity of teachers in creating an effective Arabic language learning model handbook. The research is based on potentials and problems in the field especially in the Arabic language learning model by sociodrama method. This research was conducted by research and development approach (R&D) and used ten steps of the research that formulated by Sugiyono. As a development product, it is used to provide the necessity of teachers at Senior HighSchool of An Nida’ Islamic Boarding School Wonosobo.